Hubungan Kualifikasi Coder Dengan KeakuratanKode Diagnosis Rawat Jalan Berdasarkan Icd-10Di Rspau Dr S Hardjolukito Yogyakarta 2015 - Janah, Friska Miftachul, Ibnu Mardioko, SKM.,MM, Dwi Astuti, SKM., M.Kes (2015)
Implementation of diagnosis coding should fit ICD-10 in order to obtain accurate code, it because the result of this diagnosis coding is used to index the process of recording the disease, national and international reporting morbidity and mortality, the analysis of health care financing, as well as for research and clinical epidemiology. The purpose of this study was to determine the correlation of qualified of coders with the accuracy of outpatient diagnostic codes based on ICD-10 at RSPAU dr S Hardjolukito in 2015. This study used analytic observational research with cross sectional study design. The population subject of research is all officers coders outpatient diagnostic and the population object of research a diagnostic outpatient codes that encoded by the coders in April 2015. The sample in this study to the subject sample consist of 4 people coders, while the object sample totaling 45 diagnosis using techniques of quota sampling. The analysis showed that the amount o codes that prod. Correlation of the test result using chi square test with continuity correction shows that produced by D3 Medical Record has 100% accurate, then produced by Non-D3 Medical Record there still not accurate. There is a correlation between educational background (0,001) and tenure (0,001) with the accuracy of outpatient diagnostic codes at RSPAU dr S Hardjolukito in 2015. Key word: accurate, diagnosis code, ICD-10